Sudden Cardiac Death (SCD) -One of the most difficult challenges in modern cardiology. - Islam, Md Saiful (KYAMC Journal, 2013)
DOI: http://dx.doi.org/10.3329/kyamcj.v2i1.13511 KYAMC Journal Vol.2(1) 2011 pp.92-95